PENGARUH PENGHINDARAN PAJAK, DEBT COVENANT, DAN MEKANISME BONUS TERHADAP TRANSFER PRICING - Zahira, Sarah; Ratnasari, Fina (LPPM Universitas Putera Batam, 2025)
The purpose of this study is to find out and test how Tax Avoidance, Debt Covenant, and Bonus Mechanism affect energy sector businesses listed on the Indonesia Stock Exchange for the period 2018 - 2023. This type of secondary research uses data and is quantitative associative. This research uses Microsoft Excel software and E-Views 12 is the data analysis technique used. The research population is energy sector companies listed on the Indonesia Stock Exchange in 2018 - 2023. Purposive sampling is the method used in this study to collect data, and because the population is 83 people, 5 data samples are taken. The results of these findings partially show that Tax Avoidance, Debt Covenant, and Bonus Mechanism have an effect on Transfer Pricing The findings of the study show that Tax Avoidance, Debt Covenant, and Bonus Mechanism have a simultaneous effect on Transfer Pricing.